Reporting Services Sebagai Sistem Alternatif dalam Pembuatan Laporan - Heripracoyo, Sulistyo (Bina Nusantara University, 2011)
Generally in an administrative system there are also report features for beside data entry features. One of the benefits from this report is that users do not need to know where the data is obtained by the database either directly from online transaction processing (OLTP) or historical data. Nevertheless, the report features are designed by the developer in accordance with user needs. Commonly, the application developers use additional softwares integrated to the application. This study describes an alternative report system called Reporting Services which is a software from Microsoft that can be found from SQL 2000 to the latest version. With Reporting Services creating reports can be more easy and interactive to the users, and the results can be direct accessed via the web.